Recovery of rare earth elements from mining wastewater with aminomethylphosphonic acid functionalized 3D-printed filters - Virtanen, Emilia J.; Kukkonen, Esa; Yliharju, Janne; Tuomisto, Minnea; Frimodig, Janne; Kinnunen, Kimmo; Lahtinen, Elmeri; Hänninen, Mikko M.; Väisänen, Ari; Haukka, Matti; Moilanen, Jani O. (Elsevier B.V., 2025)
Herein we report the use of nylon-12-based 3D-printed filters incorporating α-aminomethylphosphonic acid as an active additive for the recovery of Y, Nd, and Dy from the mining waste solution containing Al, K, Ca, Sc, Fe, Co, Cu, Zn, Y, Nd, Dy, and U. Nylon-12 was chosen for the polymer matrix of the filter due to its inactivity towards the studied metals. The micrometer-level structure of the filters was studied with a scanning helium ion microscope and X-ray tomography to reveal the porosity, pore size, and active additive distribution in the filters. Furthermore, FTIR spectroscopy was used to analyze the compositional changes in the 3D-printed filters after the printing and adsorption processes. Adsorption of the metals was studied at a pH range of 1–4, and the following adsorption trend Sc > Fe > U > Y, Nd, Dy > Al, Cu, Zn > K, Ca, Co was observed in each of the studied pH values. The sequential recovery process for metals was studied at pH 2, and desorption of the metals from the filters was performed with 6 M HNO3. 100 % adsorption of REEs, Fe, and U was achieved during the recovery process, and on average, over 88 % of the adsorbed Y, Nd, and Dy were desorbed from the filters. In contrast to Y, Nd, and Dy, the desorption of Sc, Fe, and U was minimal (Fe and U) or negligible (Sc) with 6 M HNO3 due to their strong coordination to the active additive. Maximum adsorption capacities for Y, Nd, Dy, and U were determined by using linear Langmuir adsorption isotherm. The best maximum adsorption capacity was determined for Sc, Qmax = 0.51 mmol/g followed by U, Nd, Dy, and Y with capacities of 0.47, 0.24, 0.23, and 0.17 mmol/g, respectively. Overall, this study achieved a complete removal of Sc, Fe, and U from the simulated mining waste solution leaving a final eluate that mainly contained Y (320 μg), Nd (350 μg), Dy (330 μg), and Al (710 μg) demonstrating the applicability of the 3D-printed filters in the recovery of Y, Nd, and Dy from the multimetal solution.